2020
DOI: 10.1021/acs.est.0c05774
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nonaqueous Liquid–Liquid Biphasic Solvent for Energy-Efficient Carbon Dioxide Capture with Low Corrosivity

Abstract: To address the problems of the relatively high energy penalty and corrosivity of aqueous biphasic solvents, a novel nonaqueous biphasic solvent composed of 2-((2-aminoethyl)­amino)­ethanol (AEEA), dimethyl sulfoxide (DMSO), and N,N,N′,N″,N″-pentamethyldiethylenetriamine (PMDETA) was proposed for CO2 capture. With optimization, this novel AEEA–DMSO–PMDETA (A–D–P) biphasic solvent could achieve a high CO2 loading of 1.75 mol·mol–1, of which 96.8% of the absorbed CO2 was enriched in the lower phase with only 49.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The phase separation behavior of nonaqueous absorbents was affected by the organic solvent polarity. Zhou et al 19 showed that the reaction products of amine with CO 2 were supposed to have high polarities and preferred to dissolve in a polar organic solvent. Yu et al 30 investigated the effects of the polarity and electronegativity of the N atom in tertiary amines on the phase separation behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase separation behavior of nonaqueous absorbents was affected by the organic solvent polarity. Zhou et al 19 showed that the reaction products of amine with CO 2 were supposed to have high polarities and preferred to dissolve in a polar organic solvent. Yu et al 30 investigated the effects of the polarity and electronegativity of the N atom in tertiary amines on the phase separation behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of phase change absorbents were used for reference, , and different kinds of nonaqueous biphase absorbents were reported. Novel nonaqueous liquid–liquid biphase absorbents comprising MEA-AMP-dimethyl sulfoxide (DMSO)- N , N , N ′, N ″, N ″-pentamethyldiethylenetriamine (PMDETA), and AEEA-DMSO-PMDETA were proposed. , Nonaqueous liquid–solid biphase absorbents comprising ethylenediamine (EDA)-ethanol, triethylenetetramine-PEG200, , potassium prolinate-ethanol, piperazine/ N , N -dimethylformamide (DMF), and EDA-DMF were investigated. Yet, to avoid solid formation and a nonlinear increase in viscosity, Chowdhury et al developed high-performance nonaqueous absorbents comprising alcohols that were in a single phase within the whole range of CO 2 loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that increasing the concentration of MEA aqueous solution was expected to reduce the energy consumption of CO 2 capture 29,30 . At present, the concentration of nonaqueous absorbents used in most studies is less than 1 mol/L, especially polyamine absorbents with high absorption capacity 18,20,21,23,31,32 . This is relatively low compared with the concentration of MEA aqueous solution (5 mol/L) in practical industrial application, so the absorption–desorption behavior of non‐aqueous organic amine absorbents at high concentration still need to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Phase-change absorbents can significantly reduce the energy consumption in the regeneration step since only CO 2 -rich phases must be regenerated. For example, Zheng et al 20 and Tao et al 21,22 proposed two excellent liquid-solid phase-changing absorbents of TETA/ethanol and TETA/PEG200 by screening several amine/organic solvent combinations, and studied their CO 2 absorption and phase-changing behavior at 0.2-1 M. Zhou et al 23 developed a nonaqueous liquid-liquid phase-changing absorbent of 2-((2-aminoethyl)-amino)ethanol (AEEA)/dimethyl sulfoxide (DMSO)/pentamethyldiethylenetriamine (PMDETA), which had a CO 2 absorption capacity of 1.75 mol/mol AEEA at 1 M, and the rich phase contributed 96.8% of the CO 2 capacity.…”
mentioning
confidence: 99%
See 1 more Smart Citation